The public functioning challenge: collaborative management as a governance strategy. The case of «Commons» and the Italian administrative solution - Pettinari, Gloria (P.A. Persona e Amministrazione, 2023)
Public activity is called to address public interest and general needs. To respond, today more than ever, the complexity of society calls for multi-level governance, so the public authority is not the only actor in that game. However, reasoning on the newest complex challenge for the public authorities, there may lead to new solution, that is administrative instruments, coming from the practical need approach to answer general interest differently. This kind of approach, from the bottom to the top, may challenge the current legal system. Following the «commons» issues, this paper seeks inspiring solutions to manage its complexity. This is because, in the «commons» experiences, we can find more groups of interests and new solutions willing to overcome some traditional boundaries between public and private power and their means: collective actions. The activities implemented for «commons» define a proper collaborative management strategy, particularly important to manage the complexity, such as the multidimensionality framework of relationships among people and authorities, their needs, and their legal instruments. To show how the Italian case of «commons» practices has come to find legal tools to manage the complexity means to show how to involve both citizens, private, and public authorities in a joint agreement, defining a common project. So, commons and collaborative governance combine in a legal system to change the traditional relationship between actors in the ‘public sphere’, where the public power has traditionally been mainly authoritative. The paradigm shifts to a collaborative relationship (from a separate one in a bipolar configuration) thanks to a proper collaborative legal regulation system, starting to recognise «subsidiarity» as a constitutional principle. This also means a cultural change or a development of values that implies legal and administrative formal solutions and organisational strategy. It can be seen as a good governance strategy for a democracy. Commons management implies dealing with complex interests, powers, and actors’ systems. So, on the one side, involving more people in conflicts with each other and on the other side finding a collaborative solution; is the best democratic way to find a tertium genus good solution (neither authoritative nor private). The is still a long way to go, but we have started to find legal methods such as administrative agreement, defining goals and responsibilities to share with more subjects in a multi- players context. The practice stimulates some legal solutions only in a democratic context where participation can be guaranteed. It seems to have become a new administration model, an organisation solution for Public Law.